Choosing Neuroanaesthesia as a career: Marching towards new horizons - Khandelwal, Ankur (Indian J Anaesth, 2021)
Anaesthesiology is an ever-changing science and amongst its sub-specialities, the field of neuroanaesthesia is making rapid strides. The fragility of the brain and spinal cord and the multitude of complexities involved in neurosurgery and interventional neuroradiological procedures demand dedicated training in neuroanaesthesia. With rapid advancement in other neuroscience specialties, neuroanaesthesia too has made outstanding progress, owing to establishment of structured training, publication of high-quality scientific research, and invention of novel medications and monitoring modalities. The opportunities for training in India and abroad and resources to broaden knowledge in neuroanaesthesia have increased over the last two decades. A career in neuroanaesthesia offers a great future for budding anaesthesiologists.